2008
DOI: 10.4103/0019-509x.44064
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with laryngeal carcinoma

Abstract: BACKGROUND: Cancer is a multifactorial disease. Repetitive cumulative damage of cellular organelles by oxy-free radicals are few of the important causative factors. AIM: To assess the role of oxidative stress in the laryngeal cancer patients in Indian population. SETTING AND DESIGN: Case control study. MATERIALS AND METHODS: Level of malondialdehyde (MDA) as a marker of oxidative stress was examined in large cohort of control (50) and laryngeal carcinoma patients (155) from North India. Both the controls and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, numerous studies demonstrated that oxidative stress directly or indirectly causes DNA damage, which is a predisposing factor to malignant lesions (14,15). The body has established appropriate self-defense mechanisms to cope with these harmful stimuli, including the KEAP1-NRF2-AREs pathway (16). KEAP1 was discovered in 1999 (17), and the KEAP1 system is constantly researched, particularly NRF2.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies demonstrated that oxidative stress directly or indirectly causes DNA damage, which is a predisposing factor to malignant lesions (14,15). The body has established appropriate self-defense mechanisms to cope with these harmful stimuli, including the KEAP1-NRF2-AREs pathway (16). KEAP1 was discovered in 1999 (17), and the KEAP1 system is constantly researched, particularly NRF2.…”
Section: Discussionmentioning
confidence: 99%
“…More than a half-million new cases of head and neck cancers are reported annually worldwide [2]. Larynx squamous cell carcinoma (LSCC) constitutes almost 2% to 3% of all malignant tumours, representing the second most common malignant neoplasm of the respiratory tract [3].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the decrease in retinol levels in cancer could be due to the increased utilization by the affected tissues or in combating the excessive oxidative stress in circulation as a result of cancer. The results of the study conducted by R.C Dwivedi [25] and his co-workers show increased lipid peroxidation in laryngeal cancer patients as a consequence of free radical generation. According to Nicholas Wald [26] and his coworkers serum retinol levels in man have predictive value for subsequent cancer, low levels being most clearly associated with an increased risk of lung cancer and gastro intestinal tract cancers.…”
Section: Discussionmentioning
confidence: 94%